Plant-parasitic nematodes and food security in sub-saharan Africa - Coyne, Danny L.; Cortada Gonzales, L.; Dalzell, J.J.; Claudius-Cole, A.O.; Haukeland, Solveig; Luambano, N.; Talwana, Herbert A.L. (Annual Reviews, 2018)
Sub-Saharan Africa (SSA) is a region beset with challenges, not least its ability to feed itself. Low agricultural productivity, exploding populations, and escalating urbanization have led to declining per capita food availability. In order to reverse this trend, crop production systems must intensify, which brings with it an elevated threat from pests and diseases, including plant-parasitic nematodes. A holistic systems approach to pest management recognizes disciplinary integration. However, a critical under-representation of nematology expertise is a pivotal shortcoming, especially given the magnitude of the threat nematodes pose under more intensified systems. With more volatile climates, efficient use of water by healthy root systems is especially crucial. Within SSA, smallholder farming systems dominate the agricultural landscape, where a limited understanding of nematode problems prevails. This review provides a synopsis of current nematode challenges facing SSA and presents the opportunities to overcome current shortcomings, including a means to increase nematology capacity.